An assessment of interest rates on high income earners in South Africa - Kotlele, Kometsi; Edoun, E. I.; Naidoo, Vinessa (Technium Social Sciences Journal, 2021)
The globalisation phenomenon has enhanced relationship between economies in the world through free market and movement across borders. In such conditions, each government should properly manage and control exchange requirements at domestic and global level through implementation of relevant monetary policies to sustain economic development. Considering the impact of the currency and interest rates on expenditure and/or revenues, this study reports on the results of real interest rates on high income households in South Africa. The study employed the use of quantitative secondary data involving interest rates. Time series data sets on three independent variables over a period of twenty years arising from 1998 to 2018 was used. The data was collected from South African Reserve Bank (SARB) and Statistics South Africa (STATSSA). The statistical bulletins, annual reports and databases were used following permission from the relevant custodians of data from SARB and STATS SA. Data analysis was done using STATA software. The study employed the use of both correlation and linear regression methods of analysis on the changes recorded on how interest rates impact on the behaviour of households for the variables under observation and these are personal transport, household credit and durable goods consumed at the household level. Research findings revealed that a negative relationship exists between real interest rates as adjusted for inflation on the overall consumption of goods in the household level. Furthermore, an increase of the interest rates leads to a decrease in spending while the decrease of interest rates leaves more money in the households for increased spending in all areas of credit consumption and in this case all research variables under study increased with a decreased real interest rate.